Climate change and dermatology: An introduction to a special topic, for this special issue - Silva, Genevieve S. (Int J Womens Dermatol, 2020)
Anthropogenic global climate change is a well-documented phenomenon that has led to average global temperatures climbing to approximately 1 °C above preindustrial (1850–1900) levels, with even higher regional deviations in some areas and significantly increased average warming in densely populated urban centers. In 2018, the United Nations Intergovernmental Panel on Climate Change set a threshold of 1.5 °C of average warming (above the preindustrial baseline), beyond which our planet will become significantly less hospitable to human life. However, adverse human health impacts are already occurring due to current levels of global climate change, as summarized by publications such as The Lancet’s annual “Countdown on Health and Climate Change,” initiated in 2016. The human health impacts of climate change are truly cross-disciplinary, with nearly every medical specialty either already facing or set to face effects. The field of dermatology is not immune to these risks. This special issue of the International Journal of Women’s Dermatology is dedicated to the cross section of dermatology and climate change. This initial article will serve as an overview to introduce readers to the topic and to lay the groundwork for the rest of the issue. We are delighted to work with the Women’s Dermatological Society and welcome their support for this dedicated issue. Herein, you will read from up-and-coming stars in the field and established experts, including articles on the following key areas: infectious diseases, environmentally friendly office practices, sunscreens and the environment, refugee health, heat-related illness, the effect of air pollution on the skin, the impact of climate change on pediatric dermatology, implications for skin cancer, and skin issues related to flooding and extreme weather events.